El Excentrico, 1965-06-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
June 05, 1965 [5 de junio de 1965]. Ano 15, No 16. Cover has a photograph of a baby Stacy Lynne Moro, with headline, "Miss Stacy Lynne Moro - Stacy! What's your name?"